2001
DOI: 10.2337/diabetes.50.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Interactive Effect of β3- and α2b-Adrenoceptor Gene Polymorphisms on Fat Mass in Caucasian Women

Abstract: /Glu 9 ␣2bAR variant on body composition and energy balance, in a large cohort of Caucasian women (n = 909). A second goal was to examine the interaction effect of Glu 12 /Glu 9 ␣2bAR and Trp64Arg ␤3AR on the same phenotypes. The obesity-related phenotypes studied were as follows: body weight, BMI, fat mass, visceral fat, fat-free mass, resting metabolic rate (RMR), VO 2max , leisure time physical activity, and daily energy intake. Body composition and body fat distribution were measured by dual-energy X-ray a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 38 publications
1
27
1
Order By: Relevance
“…For instance, an interaction effect of b3-and a2B-adrenergic receptor (ADR) genes on fat mass in Caucasian women has been observed. 8 In addition, gene-gene interaction effects between a2A-, b2-and b3-ADR gene markers on the phenotypic variability of abdominal obesity and plasma lipid levels were observed in the Quebec Family Study cohort. 7 In the present study, we investigated the interactions among polymorphisms in the b2-and b3-ADR genes on total body adiposity and abdominal fat levels in the sedentary state and in response to endurance training in the HERITAGE Family Study cohort.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, an interaction effect of b3-and a2B-adrenergic receptor (ADR) genes on fat mass in Caucasian women has been observed. 8 In addition, gene-gene interaction effects between a2A-, b2-and b3-ADR gene markers on the phenotypic variability of abdominal obesity and plasma lipid levels were observed in the Quebec Family Study cohort. 7 In the present study, we investigated the interactions among polymorphisms in the b2-and b3-ADR genes on total body adiposity and abdominal fat levels in the sedentary state and in response to endurance training in the HERITAGE Family Study cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The interactive effect of the Glu deletion (heterozygous Glu12/Glu9 allele) in the ␣ 2B -AR and a Trp64Arg polymorphism in the ␤ 3 -AR (to be described below) on energy metabolism and body composition has been examined in healthy women; a significant interaction of the ␣ 2B -and the ␤ 3 -AR variants with greater fat mass and percentage of fat was identified (Dionne et al, 2001). Such results suggest that these two AR variants interact in the regulation of body composition, but studies in larger and more ethnically diverse populations are required.…”
mentioning
confidence: 99%
“…Many studies have shown that the ADR genes are correlated with obesity-related phenotypes. These include the ADRA2B, 18,19 ADRB1, 20,21 ADRB2 18,22-29 and ADRB3 genes. 18,19,28,30,31 Remarkably, most clinically effective antipsychotic drugs are potent ADRA1 antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…These include the ADRA2B, 18,19 ADRB1, 20,21 ADRB2 18,22-29 and ADRB3 genes. 18,19,28,30,31 Remarkably, most clinically effective antipsychotic drugs are potent ADRA1 antagonists. 32 A possible role of the ADRA1A promoter region in the development of schizophrenia was found in an isolated Spanish population, 33 but not in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%